Strategi Pengembangan Usaha Home Industri Sangkar Burung Di Kecamatan Bumiratu Lampung Tengah (Studi Kasus Sangkar Burung Afta) - Billa Fajar Kurnia; Jawoto Nusantoro; Deny Edy Widodo (Universitas Muhammadiyah Metro, 2025)
A business can be developed by implementing certain strategies so that it can optimize its income. The aim of this research is to find out the internal factors of business development, find out the external factors of business development and find out the strategies that can be used to develop the afta bird cage home industry business in Bumiratu Nuban. This research applies qualitative research methods by analyzing business development strategies in the form of bird cages in the Afta bird cage home industry in Bumiratu Nuban District, Central Lampung. In collecting research data, three sources were involved who were owners of the Afta bird cage home industry and their employees. Data was obtained by conducting interviews and distributing questionnaires to determine the weight and rating on aspects of the company's internal and external factors. Data analysis in this research uses SWOT analysis which consists of Strengths, Weaknesses, Opportunities and Threats. The research results state that the S-O Strategy: (1) Maintaining product quality with quality raw materials, (2) Creating products with attractive designs, and (3) Making products using technology/machines. W-O Strategy: 1) Increasing and strengthening the marketing network, 2) Increasing capital so that it can recruit employees. 3) With adequate employees, you can meet consumer demand in large numbers. S-T Strategy: 1) Design attractive products that are no less than factory products, 2) Maintain quality products, 3) Make cages according to consumer tastes W-T Strategy: 1) Recruit employees who have creativity to meet consumer tastes, 2) Increasing promotions to attract buyers' interest.